Unexpected resilience in relict Abies pinsapo Boiss forests to dieback and mortality induced by climate change - Cortés-Molino, Álvaro; Linares, Juan Carlos; Viñegla, Benjamín; Lechuga, Víctor; Salvo-Tierra, Ángel Enrique; Flores-Moya, Antonio; Fernández-Luque, Ismael; Carreira de la Fuente, José Antonio (Frontiers Media, 2022)
Acute and early symptoms of forest dieback linked to climate warming and drought episodes have been reported for relict Abies pinsapo Boiss. fir forests from Southern Spain, particularly at their lower ecotone. Satellite, orthoimages, and field data were used to assess forest decline, tree mortality, and gap formation and recolonization in the lower half of the altitudinal range of A. pinsapo forests (850-1550 m) for the last 36 years (1985-2020). Field surveys were carried out in 2003 and in 2020 to characterize changes in stand canopy structure and mortality rates across the altitudinal range. Time series of the Normalized Difference Vegetation Index (NDVI) at the end of the dry season (derived from Landsat 5 and 7 imagery) were used for a Dynamic Factor Analysis to detect common trends across altitudinal bands and topographic solar incidence gradients (SI). Historical canopy cover changes were analyzed through aerial orthoimages classification. Here we show that extensive decline and mortality contrast to the almost steady alive basal area for 17 years, as well as the rising photosynthetic activity derived from NDVI since the mid-2000s and an increase in the forest canopy cover in the late years at mid and high altitudes. We hypothesized that these results suggest an unexpected resilience in A. pinsapo forests to climate change-induced dieback, that might be promoted by compensation mechanisms such as (i) recruitment of new A. pinsapo individuals; (ii) facilitative effects on such recruitment mediated by revegetation with other species; and (iii) a ‘release effect’ in which surviving trees can thrive with fewer resource competition. Future research is needed to understand these compensation mechanisms and their scope in future climate change scenarios.
Keywords: Deforestación - Andalucía; Climate change; Forest resilience; Ecosystem dynamics; Remote sensing; Multitemporal analysis